In Silico Analysis of Catechin, Galangin, and Hesperidin as Competitors of the SARS-CoV-2 Spike Protein - Kusumorini, Astuti; Hasna, Nisrina; Suryani, Yani; Taufiqurrahman4, Opik (UIN Sunan Gunung Djati Bandung, 2023)
Currently, Covid-19 has become endemic. However, the development of Covid-19 drugs continues to be carried out to suppress the growth of the Sars-Cov-2 virus. Some compounds with antiviral activity are catechin, galangin, and hesperidin. Angiotensin-converting enzyme-2 (ACE-2) is a protein that enters viruses into the cell. Based on that, ACE-2 can be used as a primary target to suppress the development of the Sars-Cov-2 virus. This study aimed to test the catechin, galangin, and hesperidin compounds in inhibiting the SARS CoV-2 virus from attaching to ACE-2 by trying the interactions of catechin, galangin, and hesperidin compounds with ACE-2 using the in-silico method. The material used was the three-dimensional structure of the compounds catechin, galangin hesperidin, and ACE-2. The tools used were FAF-Drugs4, Discovery Studio, and Pyrex software. Low-affinity energy values (kcal/mol) indicate promising results. The results showed that the energy affinity value of catechin was -6.2 kcal/mol, galangin was -6.3 kcal/mol, and hesperidin was -8.3 kcal/mol. This value is lower than the control affinity energy (chloroquine and favipiravir), which isÂ -5.2 kcal/mol and -4.8 kcal/mol, respectively. Based on this, catechin, galangin, and hesperidin can be used as inhibitors/competitors for the Sars-Cov-2 to attach to ACE-2.